O transportador ABC espécie-específico e o sistema de secreção do tipo IV de Brucella ovis são essenciais para modulação do tráfego e sobrevivência intracelular em macrófagos ovinos - Auricelio Alves de Macedo (2016)
Brucella ovis infection is associated with epididymitis, orchitis and infertility in rams. Information available on B. ovis and host cell interaction have been generated using murine macrophages or human epithelial cell lines, whereas the interaction between B. ovis and primary ovine macrophages has never been studied. The aim of this study was to evaluate the role of the B. ovis abcEDCBA-encoded ABC transporter and the virB operon-encoded Type IV Secretion System (T4SS) during intracellular survival of B. ovis in ovine peripheral blood monocyte-derived macrophages. B. ovis abcBA and virB2 mutant strains were unable to survive in the intracellular environment when compared to the WT B. ovis at 48 hours post infection (hpi). In addition, these mutant strains cannot exclude the lysosomal marker LAMP-1 from its vacuolar membrane, and their vacuoles did not acquire the endoplasmic reticulum marker calreticulin, which takes place in the WT B. ovis containing vacuole. Higher levels of nitric oxide production were observed in macrophages infected with WT B. ovis at 48 hpi when compared to macrophages infected with the abcBA or virB2 mutant strains. Conversely, higher levels of reactive oxygen species were detected in macrophages infected with the abcBA or virB2 mutant strains at 48 hpi when compared to macrophages infected with the WT strain. Our results demonstrate that B. ovis is able to persist and multiply in ovine macrophages, while abcBA and virB2 mutations prevent intracellular multiplication, favor phagolysosome fusion, and impair maturation of the B. ovis vacuole towards an endoplasmic reticulum-derived compartment